2017
DOI: 10.1016/j.sjpain.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Sex moderates the effects of positive and negative affect on clinical pain in patients with knee osteoarthritis

Abstract: AbstractBackground and aimsSex differences in clinical pain severity and response to experimental pain are commonly reported, with women generally showing greater vulnerability. Affect, including state (a single rating) and stable (average daily ratings over two weeks) positive affect and negative affect has also been found to impact pain sensitivity and severity, and research sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…QST measures in the included studies were PPT and temporal summation (TS) ( n = 11 studies); heat pain threshold (HPT) ( n = 10); cold pain threshold (CPT) ( n = 6). TS was examined using heat, 55,57–60 mechanical, 22,28,52 and both heat and mechanical stimuli 51,54,61 . CPM was measured in 3 studies with heat 54,57 and pressure 52 as test stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…QST measures in the included studies were PPT and temporal summation (TS) ( n = 11 studies); heat pain threshold (HPT) ( n = 10); cold pain threshold (CPT) ( n = 6). TS was examined using heat, 55,57–60 mechanical, 22,28,52 and both heat and mechanical stimuli 51,54,61 . CPM was measured in 3 studies with heat 54,57 and pressure 52 as test stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…A potential limitation of the current meta‐analysis is that data from 8 studies 51,53,54,56–59,61,102 were not pooled either due to unfitting data or absence of data in the included studies. The majority of data included in the meta‐analysis were obtained from studies conducted on individuals with knee pain, with less data available for patients with shoulder pain.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…K nee osteoarthritis (KOA) is the most common orthopaedic condition, with a prevalence of 12% to 35% in the general population and is considered to be the leading cause of disability old individuals. [1][2][3] There is still no curative treatment for KOA and only a small number of limited treatments, which aim to reduce pain and control inflammation to improve function. The treatment of KOA in the early stages includes physical therapy, [4][5][6] pain relief by nonsteroidal anti-inflammatory drugs, 7 cell-based therapy, 8,9 and intra-articular injection of hyaluronan or corticosteroids.…”
Section: See Commentary On Page 660mentioning
confidence: 99%
“…In patients with OA, differences in sex existed in the experience of pain, and psychological factors (34) and other factors, such as foot and ankle shape, footwear habit, obesity, decline in muscle strength with aging, and ligamentous laxity, may underline the differences in sex in regard to pain. In our study, female patients reported higher MFPDI scores and more disabling foot pain at baseline.…”
Section: Discussionmentioning
confidence: 99%